PELAKSANAAN ONLINE DISPUTE RESOLUTION (ODR) SETELAH BERLAKUNYA 2021 ARBITRATION RULES DAN DAMPAKNYA BAGI PARA PIHAK - Teza Salih Mauludin; Tito Adwinata; Arvin Galuh Dwiputra (Jurnal Hukum Lex Generalis, 2024)
The rise of information technology has significantly impacted the way business disputes are resolved. With a high volume of online trade, disputes can arise as frequently as they do in traditional business dealings. The increase in trading activities naturally leads to an increase in disputes that need resolution. One approach to resolving these disputes efficiently and fairly for both parties is through arbitration and alternative dispute resolution (ADR). Over time, this has evolved into Online Dispute Resolution (ODR). At a regulatory level, the implementation of ODR is guided by rules issued by the International Chamber of Commerce (ICC), which is recognized as a global authority. The issuance of the 2021 Arbitration Rules brings significant changes to the implementation of ODR. Previously, ODR required the consent of the parties, but now it is possible to carry out ODR regardless of the objections of the parties.